Antonia Mercé La Argentina and the Moving Image: Attractions and Frictions between Cinema and Dance. Issue 1 (19th January 2021) - Murga-Castro, Idoia; Marinero Labrador, Cristina
Abstract: Despite her fame and cultural prominence as a Spanish dancer, Antonia Mercé La Argentina did not appear in major film projects, like many of her peers. In this article, we examine the recent discovery of footage of Mercé and contextualize these preserved fragments within the development of Western cinema and the presence of the Spanish imaginary in the film industry of the time. These visual sources reveal how Mercé negotiated between art and technology, stage and screen, economy and aesthetics in establishing her cultural position and resisting particular constructions of Spanishness.